Toward an Adaptive Learning System Framework: Using Bayesian Network to Manage Learner Model - Nguyen, Viet Anh (International Journal of Emerging Technologies in Learning (iJET), 2012)
This paper represents a new approach to manage learner modeling in an adaptive learning system framework. It considers developing the basic components of an adaptive learning system such as the learner model, the course content model and the adaptation engine. We use the overlay model and Bayesian network to evaluate learnersâ?? knowledge. In addition, we also propose a new content modeling method as well as adaptation engine to generate adaptive course based on learnerâ??s knowledge. Based on this approach, we developed an adaptive learning system named is ACGS-II, that teaches students how to design an Entity Relationship model in a database system course. Empirical testing results for students who used the application indicate that our proposed model is very helpful as guidelines to develop adaptive learning system to meet learnersâ?? demands.